The Internet as an Educational Tool (Eurasian Research Bulletin, 2022)
This article presents the use of internet technology in learning foreign language for students that teachers can use to develop learners’ communicative competence in an EFL classroom. In this research paper we will describe about overview about internet technologies in the world. Firstly, some general information about the internet and the role of internet technologies in science and education. Also, we summarised the Internet as an educational tool.